Growth Performance of Thamari Sheep in Yemen - Al-Nokhaif, Abdullah Ali Abdullah (2009)
The production potential of the Thamari sheep as well as other native breeds in Yemen had not been well characterized and documented. A field study was conducted to demonstrate the importance of rearing sheep by farmers in Yemen, and an on station studys were conducted to evaluate the performance of the popular native Thamari sheep. The results obtained from the questionnaire survey which was carried out in 20 villages at the intermountain plains of Yemen during the first half of 2005 showed that 95% of the farmers who had cultivated land also had livestock. Sheep was the most important kind of livestock reared and for multi purpose use: as meat supplier for home consumption (100%), for producing milk (84%) and as a casual source of income for farmers (95%). Sheep was also used by farmers as exchange for goods or services (9%), and was given as gift (42%). All households surveyed kept sheep; they also reared cattle (90%), donkey, goat and camel. Data analyzed on the Thamari sheep performance consisted of 1966 records of 600 breeding ewes and 1434 lambs of 27 sires used for breeding during 12 breeding seasons over 6 years. The flock was under a restricted breeding system of two mating per year. The results showed that fertility, prolificacy and fecundity were 79%, 91% 72%, respectively, and the weight of ewe at mating was the only source of variation that significantly (p<0.01) affected these traits. Litter size at birth and weaning were 1.07, 0.94 lambs/ewe, respectively, and were significantly (p<0.05) affected by ewe genotype and postpartum weight of ewe. Sire also had significant (p<0.05) effect on litter size at birth. Litter birth weight (3.0 kg) was significantly (p<0.01) affected by year, sire, parity, litter sex composition, postpartum weight of ewe and by litter size at birth x sire interaction. Litter weaning weight and litter pre-weaning average daily gain were 16.02 kg and 145 g/d, respectively, and were significantly (p<0.01) affected by year and season of mating, sire, litter sex combination, litter size at birth, litter birth weight and postpartum weight of ewe, and by litter size at birth x sire interaction. Mortality of lamb at birth (3.0%) was significantly (p<0.01) affected by ewe genotype, while the pre-weaning mortality (4.4%) was affected by ewe genotype and birth type. Body weight of lambs at six month was 18.8 kg and was significantly (p<0.01) affected by year of birth, sex, birth type, birth weight of lamb, postpartum weight of ewe, sire and sex x birth type interaction (p<0.05). Heritability estimates for birth weight, weaning weight and pre-weaning average daily gain of Thamari lambs were 0.23 ± 0.08, 0.03 ± 0.04 and 0.02 ± 0.04, respectively. In conclusion, it is obvious that sheep are the most important kind of livestock reared by farmers and for multipurpose. Several productive traits in the Thamari sheep were found lower than average values reported in the literatures for other breeds. These could be improved by increasing number of lambs born per ewe and growth performance of lambs, which may be achieved by using an optimum mating system in parallel with improved management and feeding. Sire and ewe genotypes as well as weight of the ewe at mating and lambing were found to be the most important sources of variation affecting several productive traits in the Thamari sheep. Therefore, the contribution of the significant factors to the total phenotypic variation of the Thamari sheep performance should be eliminated before applying selection and estimating genetic parameters.